2021
DOI: 10.3389/fphar.2021.655372
|View full text |Cite
|
Sign up to set email alerts
|

Emodin Alleviates Severe Acute Pancreatitis-Associated Acute Lung Injury by Inhibiting the Cold-Inducible RNA-Binding Protein (CIRP)-Mediated Activation of the NLRP3/IL-1β/CXCL1 Signaling

Abstract: Objective: Severe acute pancreatitis (SAP) can lead to acute lung injury (ALI). This study investigated the therapeutic effect of emodin and its molecular mechanisms in a rat model of SAP-ALI.Methods: Forty male Sprague-Dawley rats were randomly divided into the groups: Control (CON), SAP (SAP), emodin (EMO), and C23 (C23). The latter three groups of rats were induced for SAP-ALI by retrograde injection of 5% sodium taurocholate into the biliary-pancreatic duct and were treated with vehicle, emodin or C23, res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
40
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(41 citation statements)
references
References 65 publications
1
40
0
Order By: Relevance
“…5E and 5F ). Because CXCL1 was found to be generated in an inflammasome-dependent mechanism in THP-1 cells ( Figure 2D ) and by other groups ( Tomalka et al , 2011 ; Xu et al , 2021 ), these data suggest that inflammasome activation is necessary for downstream amplification of the innate immune response to clozapine in vivo , as well. However, upon repeating this study using a different lot of anakinra, anakinra alone caused neutrophilia.…”
Section: Resultsmentioning
confidence: 51%
“…5E and 5F ). Because CXCL1 was found to be generated in an inflammasome-dependent mechanism in THP-1 cells ( Figure 2D ) and by other groups ( Tomalka et al , 2011 ; Xu et al , 2021 ), these data suggest that inflammasome activation is necessary for downstream amplification of the innate immune response to clozapine in vivo , as well. However, upon repeating this study using a different lot of anakinra, anakinra alone caused neutrophilia.…”
Section: Resultsmentioning
confidence: 51%
“…Plasma-derived exosomes from SAP mice were capable of triggering NLRP3-dependent pyroptosis in AMs ( Wu et al, 2020 ). Emodin might inhibit the cold-inducible RNA-binding protein (CIRP)-mediated activation of the NLRP3/IL-1β/CXCL1 signaling in rats, which then ameliorated the SAP-associated ALI ( Xu et al, 2021 ). Our study confirmed the crucial role of GSDMD-mediated pyroptosis in SAP-associated ALI.…”
Section: Discussionmentioning
confidence: 99%
“…Pyroptosis or gasdermins are involved in several diseases, including viral or bacterial infections, autoinflammatory genetic diseases, complex diseases exacerbated by inflammation, and cancer; inhibiting pyroptosis or gasdermins is a promising strategy to intervene in these diseases ( Liu et al, 2021 ). However, only very few studies focused on the role of pyroptosis in SAP-associated ALI ( Wu et al, 2020 ; Gao et al, 2021 ; Xu et al, 2021 ). It is unclear whether the targeted therapy of pyroptosis will be effective.…”
Section: Introductionmentioning
confidence: 99%
“…Xu et al . further determined that emodin (40 mg/kg) markedly mitigated SAP-upregulated cold-inducible RNA-binding protein expression and NLRP3 inflammasome formation to attenuate progressive pulmonary neutrophil infiltration in SAP-ALI rats, via deactivating NLRP3/IL-1β/CXCL1 signal [ 49 ]. Pyroptosis has recently been well-characterized as inflammasome-related programmed cell death and gasdermin D is defined as an executioner for pyroptosis downstream of inflammasome activation.…”
Section: Pharmacological Effects Of Emodinmentioning
confidence: 99%